2014
DOI: 10.1371/journal.pone.0089412
|View full text |Cite
|
Sign up to set email alerts
|

Protein Malnutrition Impairs the Immune Response and Influences the Severity of Infection in a Hamster Model of Chronic Visceral Leishmaniasis

Abstract: Leishmaniasis remains one of the world's most devastating neglected tropical diseases. It mainly affects developing countries, where it often co-exists with chronic malnutrition, one of the main risk factors for developing the disease. Few studies have been published, however, on the relationship between leishmaniasis progression and malnutrition. The present paper reports the influence of protein malnutrition on the immune response and visceral disease development in adult hamsters infected with Leishmania in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 34 publications
(42 reference statements)
0
28
1
Order By: Relevance
“…Both short and long time of protein deprivation disrupt some blood parameters (e.g. decreased hemoglobin level, MCV, MCH), impair immune functions and increase sensitivity to infections [ 6 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both short and long time of protein deprivation disrupt some blood parameters (e.g. decreased hemoglobin level, MCV, MCH), impair immune functions and increase sensitivity to infections [ 6 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…which further leads to secondary damage to an already injured CNS . Protein malnutrition impairs the immune systems response and results in a decreased ability to produce antibodies and cytokines . Protein energy malnutrition can impair the proliferation of CD8 T lymphocytes responsible for suppressing infection .…”
Section: Techniquementioning
confidence: 99%
“…48,49 Protein malnutrition impairs the immune systems response and results in a decreased ability to produce antibodies and cytokines. 50,51 Protein energy malnutrition can impair the proliferation of CD8 T lymphocytes responsible for suppressing infection. 52 In the neurosurgical patient, a superficial wound infection can have potentially catastrophic complications, such as meningitis.…”
Section: Nutritionmentioning
confidence: 99%
“…Although literature suggests predominance of the disease in male gender 19 , our data are in accordance with the results of Queiroz et al 's study 20 , who found the same distribution of the disease between children of both genders. An important risk factor of severe VL is malnutrition 21 . In this study, most of the recruited patients had normal nutritional status based on the weight-for-age indicator in the WHO growth charts ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%